Noble-metal mineralization in olivine clinopyroxenite within idgimskiy gabbro-peridotite-pyroxenite complex (West Sayan Mountains); IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Cherkasova T. Yu. Tamara Yurievna (Mineralogy, Geochemistry and Petrography, 2014)
Title screen